2018
DOI: 10.1093/nar/gky129
|View full text |Cite
|
Sign up to set email alerts
|

Translational profiling of B cells infected with the Epstein-Barr virus reveals 5′ leader ribosome recruitment through upstream open reading frames

Abstract: The Epstein-Barr virus (EBV) genome encodes several hundred transcripts. We have used ribosome profiling to characterize viral translation in infected cells and map new translation initiation sites. We show here that EBV transcripts are translated with highly variable efficiency, owing to variable transcription and translation rates, variable ribosome recruitment to the leader region and coverage by monosomes versus polysomes. Some transcripts were hardly translated, others mainly carried monosomes, showed rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 68 publications
(72 reference statements)
1
37
0
Order By: Relevance
“…The HSV-1 genome is about 152kb in size and known to encode at least 80 open reading frames (ORFs), many of which have been extensively studied. Large-scale RNA-seq and ribosome profiling recently revealed that the coding capacity of three other herpesviruses, namely human cytomegalovirus (HCMV), Kaposi's sarcoma-associated herpesvirus (KSHV) and Epstein-Barr Virus (EBV) is significantly larger than previously thought [2][3][4][5] . For HCMV and KSHV, in particular, hundreds of new viral gene products were identified.…”
Section: Mainmentioning
confidence: 98%
“…The HSV-1 genome is about 152kb in size and known to encode at least 80 open reading frames (ORFs), many of which have been extensively studied. Large-scale RNA-seq and ribosome profiling recently revealed that the coding capacity of three other herpesviruses, namely human cytomegalovirus (HCMV), Kaposi's sarcoma-associated herpesvirus (KSHV) and Epstein-Barr Virus (EBV) is significantly larger than previously thought [2][3][4][5] . For HCMV and KSHV, in particular, hundreds of new viral gene products were identified.…”
Section: Mainmentioning
confidence: 98%
“…Laborious follow-up molecular work revealed the transcriptional architecture of individual genomic loci, but for most HHV-6 genes annotations are still based on these initial in-silico ORF predictions. In recent years, major advances in high-throughput sequencing approaches have revealed that the transcriptome and translatome of herpesviruses are extremely complex, encompassing large numbers of overlapping transcripts, extensive splicing and many non-canonical translation products (Arias et al, 2014;Balázs et al, 2017;Bencun et al, 2018;Depledge et al, 2019;Gatherer et al, 2011;Kara et al, 2019;O'Grady et al, 2019O'Grady et al, , 2016Tombácz et al, 2017;Whisnant et al, 2019). Our own work in which we employed ribosome profiling and systematic transcript analysis to decipher HCMV genome complexity revealed a rich collection of coding sequences that include many viral short ORFs (sORFs), uORFs and alternative translation products that generate extensions or truncations of canonical proteins (Stern-Ginossar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The annotation of HHV-6 coding capacity has traditionally relied on open reading frame (ORF)-based analyses using canonical translational start and stop sequences and arbitrary size restriction to demarcate putative protein-coding genes, resulting in a list of around 100 ORFs for each virus (Dominguez et al, 1999;Gompels et al, 1995;Gravel et al, 2013). In recent years, genome wide analysis of herpesviruses using short RNA sequencing (RNA-seq) reads, and recently also direct and long-read RNA-seq revealed very complex transcriptomes Depledge et al, 2019;Gatherer et al, 2011;Kara et al, 2019;O'Grady et al, 2019O'Grady et al, , 2016Tombácz et al, 2017), and combined with genome-wide mapping of translation, revealed hundreds of new viral ORFs (Arias et al, 2014;Bencun et al, 2018;Stern-Ginossar et al, 2012;Whisnant et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Harringtonine functions as an inhibitor of eukaryotic translation by blocking the large ribosomal subunit (Fresno et al 1977). The compound also inhibits translation of Epstein-Barr virus and influenza virus and has been used for translational profiling experiments (Bencun et al 2018;Machkovech et al 2019). Harringtonine blocked translation of CHIKV nsPs and inhibited viral RNA synthesis and subsequent production of structural proteins, indicating that the compound inhibits early viral translation events (Kaur et al 2013).…”
Section: Targeting Host Factors Involved In Chikv Replicationmentioning
confidence: 99%